2020
DOI: 10.7150/thno.46833
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for adverse clinical outcomes with COVID-19 in China: a multicenter, retrospective, observational study

Abstract: Background:The risk factors for adverse events of Coronavirus have not been well described. We aimed to explore the predictive value of clinical, laboratory and CT imaging characteristics on admission for short-term outcomes of COVID-19 patients. Methods: This multicenter, retrospective, observation study enrolled 703 laboratory-confirmed COVID-19 patients admitted to 16 tertiary hospitals from 8 provinces in China between January 10, 2020 and March 13, 2020. Demographic, clinical, laboratory data, CT imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
98
5
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(127 citation statements)
references
References 27 publications
17
98
5
6
Order By: Relevance
“…The CT severity score in the first method (Chang et al, 2005) is a semiquantitative index for estimating the involvement of the lung, which is related to the number of involved lobes and the extent of the lesions: the larger the score, the higher the risk of future development of severe COVID-19. The effectiveness of the CT severity score in the early prediction of COVID-19 progression was validated by some COVID-19 studies (Feng et al, 2020;Li et al, 2020b;Xu et al, 2020;Zheng, 2020). In addition, the CT severity score has also been proposed for prognosis and mortality prediction in acute Middle East respiratory syndrome (Das et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…The CT severity score in the first method (Chang et al, 2005) is a semiquantitative index for estimating the involvement of the lung, which is related to the number of involved lobes and the extent of the lesions: the larger the score, the higher the risk of future development of severe COVID-19. The effectiveness of the CT severity score in the early prediction of COVID-19 progression was validated by some COVID-19 studies (Feng et al, 2020;Li et al, 2020b;Xu et al, 2020;Zheng, 2020). In addition, the CT severity score has also been proposed for prognosis and mortality prediction in acute Middle East respiratory syndrome (Das et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…As the assay uses similar specimen collection and nucleic acid extraction methods as the CDC and other RT-qPCR assays, it is subjected to the same potential limitations with regard to the availability of personal protective equipment, extraction kits and reagents. Therefore, many clinicians have proposed that computed tomography (CT) scans should be a necessary auxiliary diagnostic method 52 - 56 . To identify and quarantine patients at an early date, patients clinically diagnosed by chest CT with typical ground-glass lung opacities were also counted as confirmed cases beginning in early February 57 - 60 .…”
Section: Diagnosticsmentioning
confidence: 99%
“…The potential prognostic role of CT-based assessment of lung disease extension has been suggested [13][14][15][16]27], and a few studies have included it in combined prognostic models [17][18][19][20]. Colombi et al found a slightly higher increase in AUC (from 0.83 to 0.86) when adding CT disease extension to a clinical model predictive of intensive care unit admission and/or death [17].…”
Section: Both Models Performed Better In Less Severe Patients In Termmentioning
confidence: 99%
“…The few studies that combined clinical, laboratory, and CT ndings in predictive prognostic models [17][18][19][20] showed inconsistent results: some suggested a better performance of the model when adding CT [17], others showed that CT ndings had insu cient prognostic power to be selected in multivariable models [19].…”
Section: Introductionmentioning
confidence: 99%